2014
DOI: 10.1177/0218492313516777
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic intrathoracic tracheobronchial injuries: A study of 78 cases

Abstract: Early recognition and expedient appropriate management are essential in these potentially lethal injuries. Operative management can be achieved with acceptable mortality, and conservative treatment should be considered as a valuable alternative to the well-established surgical treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 21 publications
(49 reference statements)
0
20
0
2
Order By: Relevance
“…Hewett in 1876 first described continuous drainage of the chest through an intercostal tube, numerous techniques of insertion of TT, associated complications and their management have been described. [9] Clinical assessment of tracheobronchial rupture is followed by conservative measures [10] before bronchoscopy and include antibiotic administration, symptoms relief with subcutaneous needle or chest tube to release pneumothorax and avoiding vigorous cough. [1] Fiberoptic bronchoscopy is the best method to confirm the diagnosis and to determine the exact location and extent of the lesion.…”
Section: Discussionmentioning
confidence: 99%
“…Hewett in 1876 first described continuous drainage of the chest through an intercostal tube, numerous techniques of insertion of TT, associated complications and their management have been described. [9] Clinical assessment of tracheobronchial rupture is followed by conservative measures [10] before bronchoscopy and include antibiotic administration, symptoms relief with subcutaneous needle or chest tube to release pneumothorax and avoiding vigorous cough. [1] Fiberoptic bronchoscopy is the best method to confirm the diagnosis and to determine the exact location and extent of the lesion.…”
Section: Discussionmentioning
confidence: 99%
“…Two recent case series have shown that selective conservative management of traumatic tracheobronchial injuries is possible with comparable outcomes to surgical repair [72,73]. Patients amenable to conservative management include those with stable vital signs, effective ventilation if intubated or absence of respiratory distress if breathing spontaneously, nonprogressive mediastinal and/or subcutaneous emphysema, and absence of associated esophageal or major vascular injury.…”
Section: Operative Indications In the Hypoxic Patientmentioning
confidence: 99%
“…In these patients, management includes chest tube drainage, prophylactic antibiotics, and observation. Efforts should be made to characterize the nature of the injury using rigid or flexible bronchoscopy, prior to committing to a course conservative management, as large communication with the mediastinum may place the patient at risk for mediastinitis and should be considered an indication for surgical repair [73]; some authors are using CT virtual bronchoscopy for this purpose [72].…”
Section: Operative Indications In the Hypoxic Patientmentioning
confidence: 99%
“…В то же время в публикациях отсутствуют четкие данные о частоте этого осложнения [1-3, 6, 8, 11, 17]. Большая часть статей представляет случаи из практики либо небольшие серии наблюдений, иллюстрирующие различные, по мнению авторов, механизмы появления постинтубационных дефектов трахеи; в этих публикациях также поразному трактуются показания к хирургическому и консервативному лечению этой группы тяжелобольных [2,4,7,8,11,16,17].…”
unclassified
“…Другие отечественные источники приводят данные о единичных клинических наблюдениях постинтубационных повреждений трахеи [1,2,4]. Англоязычная литература включает ряд публикаций о больших группах пациентов с постинтубационным разрывом трахеи [8,9,13,17,18], но в большинстве статей все же описаны единичные случаи из практики [11,14,15,16].…”
unclassified